Psychometric Properties of Jordanian Version of the Gilliam Autism Rating Scale -Third Edition Based on DSM-5 - Salah Aldeen Mohammad (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
The current study aims to examine the validity and reliability of Arabic Jordanian Version of Gilliam Autism Rating Scale -Third Edition. The sample consisted of (150) children aged between (3-17) years. Thus, they were divided into (50) autism, (50) mental retardation, and (50) normal. The scale was translated to Arabic language. The validity of the scale was verified by arbitrators and a concurrent validity of the scale through finding its correlation coefficients with Jordanian Version of Autistic Behavior Checklist (ABC). The reliability was calculated by using the internal consistency. The internal consistency of the scale was verified via finding the reliability coefficients for the scale dimensions and the scale as a whole, by using the Cornbrash's alpha equation and the test-retest method. Also, the reliability was calculated by correlating the item with a dimension which belongs, by using the correlation coefficient. The results of the study indicated that the scale is characterized by high and good validity and reliability indicators in the Jordanian environment.